Beliefs of Elementary School teachers about reading literary texts (Research, Society and Development, 2022)
Teachers' beliefs about reading texts go through the academic training process, through guidelines and documents, which guide, standardize and define essential knowledge for the teaching and learning process in the country, in addition to their experiences and classroom practices. The present work intends to investigate the beliefs of elementary school teachers from public schools in Santa Maria, in Rio Grande do Sul, about reading literary texts. The research has a qualitative approach, based on the analysis of questionnaires intended for teachers, for this, the characterization of the research is through the method of Exploratory Analysis, Critical Discourse Analysis based on the book Discourse and Social Change by Norman Fairclough and the Systemic-functional grammar of the Portuguese language. The conclusion of the research, after analyzing the answers, all participating teachers believe that reading literary texts is an important practice in the classroom.